Somatic Cell and Cheesemaking Variables of WAD Goat Milk: Influence of Parity and Lactation Stage - A. T. Yusuff; A. A. Badmos; E. V. Awofadeju; A. A. Akintunde; O. I. Alli; V. O. Chimezie; T. R. Fayeye (Tropical Animal Science Journal, 2021)
The suitability of any goat breed for dairy purposes depends on its assessment of milk-related traits. This study evaluates the influence of parity and lactation stage on somatic cell count (SCC) and cheese-making variables of West African Dwarf (WAD) goat milk. A total of 48 lactating WAD does of three different parities (the 1st, 2nd, and 3rd) were milked over a period of time-phased into three stages of lactation (early, mid, and late). The milk was subjected to SCC and cheese-making during which coagulation time, cheese yield (CY), whey volume, and whey pH were recorded. Collected data were subjected to analysis of variance and Pearsons’ correlation. The result revealed that the milk SCC of the does in the 3rd parity (2.16 x 105 cells) was significantly (p<0.05) higher than 1.89 x 105 and 1.87 x 105 cells in the milk of the 1st and the 2nd parity does respectively. There was a similar variation trend of SCC as lactation progresses in each of the parities. The CY significantly increased (p<0.05) as lactation progresses in the 1st parity (early – 16.95%; mid – 17.21%; late – 20.85%) while, the milk of the 2nd and the 3rd parity from mid to late lactation stage yielded statistically similar cheese that was comparable with late lactation CY of the 1st parity does. The lactation stage and SCC were positively correlated with CY. The volume and pH of the whey were neither affected by the lactation stage nor parity. The study concludes that parity uncovers the effect of lactation stage on the milk SCC of WAD does while the milk obtained from mid to late lactation stage yields more cheese.